Accessibility parameters of psychological assistance for children and their parents (according to the activity of the children’s helpline) - O. V. Kuchmaeva; L. A. Davletshina (Вестник университета)
The purpose of this article is to develop a methodology for analyzing the availability of children’s helpline services. This article is the first part of publications devoted to methodological approaches and analysis of the activities of the children’s helpline. The relevance of the work is due to the importance of psychological support in the system of assistance to children who find themselves in a difficult life situation. The complication of social ties in the modern world, in which children are growing up and socializing, the emergence of new risks, contributes to the demand for psychological help.The importance of developing a network of psychological services and, in particular, helplines that provide assistance to children and parents, as well as ensuring the availability of their services, is reflected in the strategic documents of social policy in the interests of children. The article considers the essence of the category “accessibility” in relation to the psychological service of the helpline, which allowed us to form a methodology for analysis. A methodology for analyzing information on the availability of emergency psychological care for children and parents via a children’s helpline is presented, a system of quantitative indicators characterizing the availability of children’s helpline services is proposed. Indicators are proposed that will characterize the availability of a children’s helpline from the position of working hours and indicators of the availability of psychological assistance of a children’s helpline in the context of the federal districts of Russia. The service availability coefficients were grouped.